Analysis of Regional Financial Capability and Independence and its Relation to Economic Growth in Jambi City - Deby Anggun Sari; Liona Efrina; Deki Irawan (Badan Pengelola Usaha (BPU) Universitas Jambi, 2023)
This research aims to determine the regional financial capacity in Jambi City in 2003-2021, to find out the regional financial independence in Jambi City in 2003-2021 and to know the relationship between the ability and independence of regional finance with economic growth in Jambi City from 2003-2021. The research method used to determine the regional financial capacity of the City of Jambi in 2003-2021 by calculating using the ratio of fiscal decentralization, regional financial independence measurement parameters is the regional independence ratio and looking for the relationship of ability and regional financial independence with economic growth using Pearson correlation analysis. The results of this study indicate that: (1) Jambi City has not been able in the financial capacity of the region; (2) The level of independence is still very low and shows an instructive relationship pattern; (3) The Relationship between Regional Capability and Financial Independence with Economic Growth has a very strong positive correlation. For the significance of the results of the correlation of ability and financial independence of regions with economic growth has a significant relationship.